"I’m Bright Enough to Do It, Even Though Sometimes I Feel I Can’t Do It": Perspectives of High School Students with Learning Disabilities About Existing Supports to Achieve Graduation - Connor, David J.; Cavendish, Wendy; Hallaran, Armineh; Olander, Louis (Disability Studies Quarterly, 2020)
Little evidence exists about how students with Learning disabilities (LD) recognize, understand, and utilize existing supports to ensure successful graduation from high school. In this article we ask: What are the supports available to high school students with LD that help them graduate? (a) What/who are some school-based supports they identify? (b) What/who are some non-school supports they identify? We share data from semi-structured interviews with forty high school students. Findings reveal: teacher support in the form of pedagogical choices, individualized support, and after-school support; counseling expertise in the form of academic advisement and emotional support; effective family-school collaboration; discrete family support outside of school; and various forms of self sustenance. Implications of these findings are discussed before recommendations are made to various stakeholders in the school community with the view to improving supports of students with LD toward helping them successfully graduate.